2018
DOI: 10.1186/s40550-018-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment and heavy metal contamination levels in vegetables from Tamale Metropolis, Ghana

Abstract: Background: One major route of heavy metal exposure/ accumulation to humans is via vegetable consumption. The study assessed the levels of heavy metals and their associated health risk in frequently consumed vegetables in the Tamale Metropolis. Results: Cadmium concentration in cabbage, carrot, green pepper, onion and tomato ranged from 0.04 to 0.07 mg kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
87
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 30 publications
13
87
3
4
Order By: Relevance
“…The average daily intake (ADI) of heavy metal was calculated as described in previous report [6]. The chemometric model where Cm is the measured heavy metal concentration in the vegetable presented in Table 4 a limit taken from FAO/WHO [25][26][27], also in Table 4.…”
Section: Average Daily Intake (Adi)mentioning
confidence: 99%
See 3 more Smart Citations
“…The average daily intake (ADI) of heavy metal was calculated as described in previous report [6]. The chemometric model where Cm is the measured heavy metal concentration in the vegetable presented in Table 4 a limit taken from FAO/WHO [25][26][27], also in Table 4.…”
Section: Average Daily Intake (Adi)mentioning
confidence: 99%
“…The agricultural agents have led to release of heavy metals in the environment [5]. Health of population is impaired as people ingest foods contaminated by heavy metals [6]. The presence of heavy metals in the environment has become a major threat to plant, animal and human life due their bioaccumulating tendency and toxicity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are other reports, here in Ghana that indicate low health concern for cadmium in the selected samples studied [64]. In China, studies have shown acceptable limits (HQ < 1) at certain sites with hazard quotient of cadmium in vegetables ranging from 0.2 to 0.49 [61].…”
Section: Polycyclic Aromatic Hydrocarbon Levels In Selected Samplesmentioning
confidence: 58%